Determination of the coordinate dependence of a pinning potential from the microwave experiment with vortices
The measurement of the complex impedance response and accompanied power absorption P(ω) in the radiofrequency and microwave ranges represents a most popular experimental method to investigate pinning mechanisms and the vortex dynamics in type-II superconductors. In the theory, the pinning potential (PP) well for a vortex must be a priori specified in order to subsequently analyze the measured data. We have theoretically solved the inverse problem at T = 0 K and exemplify how the coordinate dependence of a PP can be determined from a set of experimental curves P(ω|j0) measured at subcritical dc currents 0 < j0 < jc under a small microwave excitation j1